Perceptions of land tenure security in pastoral areas of Marsabit, Kenya - Otieno, Ken (RECONCILE, 2024)
A presentation made at a regional roundtable at the Colloquim on (Agro)Pastoralism, Senegal, 12-14th November, 2024.